2023
DOI: 10.1097/md.0000000000034385
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of aprepitant for the prevention of postoperative nausea and vomiting: A meta-analysis

Abstract: Background: Postoperative nausea and vomiting (PONV) is one of the common adverse reactions after surgery. Recent randomized controlled trials (RCTs) investigating antiemetic drugs suggest that aprepitant has the strongest antiemetic effect of any single drug. This meta-analysis aimed to explore the efficacy of aprepitant for preventing PONV based on the existing literature. Methods: To identify RCTs investigating the use of aprepitant for PONV preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(143 reference statements)
0
0
0
Order By: Relevance
“…Ainda existem outros antagonistas do receptor NK1, porém não foram liberados para uso na NVPO ou não apresentam tanta eficácia. (Liu et al, 2023) Os antagonistas do receptor H1 da histamina têm uma eficácia particular no tratamento de náuseas e vómitos precipitados pelas vias vestibulares, com benefício documentado no tratamento do enjoo de procedimentos cirúrgicos para estrabismo ou envolvendo o ouvido médio. Anti-histamínicos como dimenidrinato e difenidramina possuem eficácia antiemética semelhante à relatada para dexametasona, droperidol e antagonistas 5-HT3.…”
Section: Resultsunclassified
“…Ainda existem outros antagonistas do receptor NK1, porém não foram liberados para uso na NVPO ou não apresentam tanta eficácia. (Liu et al, 2023) Os antagonistas do receptor H1 da histamina têm uma eficácia particular no tratamento de náuseas e vómitos precipitados pelas vias vestibulares, com benefício documentado no tratamento do enjoo de procedimentos cirúrgicos para estrabismo ou envolvendo o ouvido médio. Anti-histamínicos como dimenidrinato e difenidramina possuem eficácia antiemética semelhante à relatada para dexametasona, droperidol e antagonistas 5-HT3.…”
Section: Resultsunclassified
“…It is a frequent postoperative complication with debilitating impacts, such as excruciating pain that lowers patient satisfaction and extends patient's stay at the hospital. 1 The severe effects associated with the PONV lead to unplanned readmissions that place a significant financial burden on the family members. In addition to these negative effects, Unsal et al posited that PONV may result in other problems, including higher medication costs, severe bleeding, aspiration pneumonia and electrolyte imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the superior effectiveness of Palonosetron over Ondansetron in the prevention of PONV, with similar incidences of adverse effects [9]. Additionally, a meta-analysis on the efficacy of Aprepitant for PONV prevention highlighted its significant role in reducing the occurrence of PONV, although its effects on postoperative analgesia require further exploration [10].…”
Section: Discussionmentioning
confidence: 99%